Avaliação da ação anorexígena do 4, 4’-dicloro difenil disseleneto em ratos - Bortolatto, Cristiani Folharini (2015)
Obesity is an ever-increasing health concern of global importance. Despite that, treatment options remain limited leading to a constant search for therapies well tolerated and efficacious. Based on several biological actions described for diorganoyl diselenides, the objective of this thesis was to investigate the anorexigenic potential of diphenyl diselenide [(PhSe)2] and p-chloro-diphenyl diselenide [(p-ClPhSe)2] in rats. The results of the first protocol showed that the intraperitoneal administration of diselenides to rats produced an anorexigenic action and body weight reduction. The anorexigenic action induced by diselenides resulted in reduction of the frequency, mean duration and mean size of meals and was accompanied by a classic behavioral satiety sequence (BSS) profile with an earlier-than-normal onset of satiety. The findings suggest that diselenides caused a satiating action which was related to the hypothalamic serotonin uptake inhibition. Besides, the results of the second protocol revealed that dietary supplementation with (PhSe)2 and (p-ClPhSe)2 also reduced the food intake and body weight of rats. Anorexigenic action observed in rats exposed to diets supplemented with (p-ClPhSe)2 was dependent on the concentration used and previous experience. The first contact with a diet containing (p-ClPhSe)2 caused a satiating action characterized by an advance in the resting onset and preservation of the temporal components of BSS as well as reduction of the frequency, mean duration and mean size of meals. However, the second exposure to a diet containing (p-ClPhSe)2 caused pronounced changes in the meal pattern and BSS disruption, suggesting that it produces aversive effects. This hypothesis was confirmed trough a standard conditioned taste aversion test. Furthermore, preference by the control diet in a choice experiment suggests that (p-ClPhSe)2 can alter the food palatability. Thus, in addition to a satiating action, the anorexigenic action of (p-ClPhSe)2 seems to be related to the appearance of malaise and atypical taste. Lastly, findings of the third protocol demonstrated that acute anorexigenic action of (p-ClPhSe)2 can be related with reduction of hypothalamic expression of neuronal nitric oxide synthase and two orexigenic neuropeptides, melanin-concentrating hormone and orexin. A reduction of orexin levels was also found for repeated treatment with (p-ClPhSe)2. However, the repeated treatment with (p-ClPhSe)2 induced endoplasmic reticulum stress and apoptosis in hypothalamus and liver revealing its cytotoxic effect. Associated with these processes, alterations of protein content related with cell stress and survival/death events were found. In accordance with the results, (p-ClPhSe)2 caused a hypophagic action by exerting therapeutic actions but also by triggering toxic effects. In conclusion, data set of the present thesis demonstrates the anorexigenic and body weight reducing potential of (PhSe)2 and (p-ClPhSe)2 in rats. Moreover, the results suggest that (p-ClPhSe)2 reduces food consumption through multiple mechanisms including satiety induction, changes in the food palatability and appearance of malaise/toxicity.